The agreement in accuracy between tomograms, resistograms and the actual condition of the wood from lime trees harvested from cities - MUȘAT Elena Camelia (BioResources, 2023)
The internal quality of the wood is one of the main factors affecting the stability of trees, and it has always been of great interest to science and practice. For this reason, the present study aims to compare the results obtained by wood tomograms with those of resistance to drilling and the visual appearance after cutting a slice with a chain-saw, both to evaluate the presence and dimensions of the inside defects, and also to evaluate the irregularities of the wood structure. Round pieces of lime wood harvested from public areas were used for comparison by taking sound tomograms, followed by taking resistograms on two perpendicular directions at the same level. The results showed that internal wood defects are not always the ones that lead to reduced speeds of sound propagation through the wood. In addition, there were instances in which changes in the internal structure of the wood led to improperly colored tomograms, namely the sections characterizing the point of insertion of a thick branch in the trunk, where the tomograms indicated low speeds of sound transfer through the wood in the stem and high speeds in the wood of the branch.
Keywords: Sound tomograms; Power drill machine; Relative resistance to drilling; Lime trees; Wood quality; Internal defects